2020
DOI: 10.1029/2020jc016406
|View full text |Cite
|
Sign up to set email alerts
|

A New Ensemble‐Based Approach to Correct the Systematic Ocean Temperature Bias of CAS‐ESM‐C to Improve Its Simulation and Data Assimilation Abilities

Abstract: The persistent biases that are associated with the mean state in coupled or climate models can cause simulation problems and degrade the results of seasonal to decadal climate predictions by affecting the variability of the model (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 84 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…for these purposes addressing the above limitations, could utilize other methods explicitly accounting for parameter-bias in the data-assimilation scheme to obtain a better accuracy (e.g., Dee and Da Silva, 1998;Sørensen and Madsen, 2004;Chepurin et al, 2005;Auligné et al, 2007;Li et al, 2009;Du et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…for these purposes addressing the above limitations, could utilize other methods explicitly accounting for parameter-bias in the data-assimilation scheme to obtain a better accuracy (e.g., Dee and Da Silva, 1998;Sørensen and Madsen, 2004;Chepurin et al, 2005;Auligné et al, 2007;Li et al, 2009;Du et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also considerable bias in the assimilation system due to the inadequate consideration of the subsurface ocean state in the assimilation process. Recently, the assimilation system based on CAS‐ESM‐C has been improved through bias correction (Du et al., 2020) and SSH assimilation, as presented in this paper.…”
Section: Data Model and Experimental Designmentioning
confidence: 99%
“…C is a matrix whose columns/lines are correlation functions that is adopted to localize the background error covariance. Followed by our previous studies (Dong et al., 2016; Du et al., 2020; Lu et al., 2016), the Gaussian correlation function is used. The correlation length scale is set to 400 km which is the same all over the model domain.…”
Section: Data Model and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In the evaluation of the ocean data assimilation system in CAS-ESM-C, we found that adjustments in the current field are not significant when assimilating the SST [53], but when assimilating the Argo profiles (the configuration had been changed to suit 3D data, is not same as for SST), the adjusted current field and the model biases have a great influence on the assimilation, even resulting in a simulation that cannot be effectively improved by the assimilation. For this reason, we designed a new bias correction approach to deal with the effects of model biases on the assimilation of ocean observations [54]. Therefore, the main purpose of this study was to compare the effect of this new bias correction approach with the original EnOI approach for bias correction and investigate the reasons for the differences between these two approaches, especially the current inconsistent adjustments.…”
Section: Introductionmentioning
confidence: 99%